Surfactant Administration Through Laryngeal or Supraglottic Airways (SALSA): A Viable Method for Low-Income and Middle-Income Countries - Zapata, Henry A.; Fort, Prem; Roberts, Kari D.; Kaluarachchi, Dinushan C.; Guthrie, Scott O. (Frontiers in Pediatrics, 2022)
Administration of liquid surfactant through an endotracheal tube for the treatment of respiratory distress syndrome has been the standard of care for decades. A skilled health care provider is needed to perform this procedure. In lower-income and middle-income countries (LMICs), healthcare resources are often limited, leading to increased mortality of premature infants, many of whom would benefit from surfactant administration. Therefore, having a simplified procedure for delivery of surfactant without the need for advanced skills could be life-saving, potentially diminish gaps in care, and help ensure more equitable global neonatal survival rates. Modifications to the standard approach of surfactant administration have been put into practice and these include: INtubation-SURfactant-Extubation (INSURE), thin catheter surfactant administration (TCA), aerosolized surfactant, and surfactant administration through laryngeal or supraglottic airways (SALSA). Although there is a need for larger studies to evaluate the comparative effectiveness of these newer methods, these methods are being embraced by the global community and being implemented in various settings throughout the world. Because the SALSA technique does not require laryngoscopy, a skilled provider is not required for the procedure. Therefore, because of the ease of use and safety profile, the SALSA technique should be strongly considered as a viable method of delivering surfactant in LMICs.